Accelerated precipitation and growth of phases in an Al-Zn-Mg-Cu alloy processed by surface abrasion. (1st June 2017) - Wang, Shan-Shan; Jiang, Jian-Tang; Fan, Guo-Hua; Panindre, A.M.; Frankel, G.S.; Zhen, Liang
Abstract: The surface microstructure and its evolution during long-term room-temperature storage were studied using transmission electron microscopy for an Al-Zn-Mg-Cu alloy processed by surface abrasion with grinding paper. An altered surface layer (ASL) with thickness of 0.4–0.8 μm was present on the alloy after abrasion. Ultrafine subgrains with width of about 50–120 nm and a high density of dislocations were observed in the ASL. The pre-existing aging-induced η′ and η precipitates dissolved during surface abrasion. During room-temperature aging, relatively pure Zn, Al2 Cu and AlCu phases were observed to precipitate at the extreme surface and subgrain boundaries in the ASL. These phases are very unusual in that they are typically not formed in Al-Zn-Mg-Cu alloys. Mg was not found in these particles, as it remained dissolved in the solid solution of the ASL. Al2 Cu and AlCu phases also precipitated at the grain boundaries in the underlying substrate right below the ASL, as far as 6 μm in depth from the extreme surface. Considerable growth and coarsening of these phases occurred during natural aging over a period of 42 months. The enhanced diffusion accelerated by vacancies, dislocations, and subgrain/grain boundaries was considered to be mainly responsible for the accelerated precipitation and growth of these atypical phases. Graphical abstract: Image 1